2008
DOI: 10.1111/j.1477-8947.2008.00213.x
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability assessment of national rural water supply program in Tanzania

Abstract: Sustainability of rural water supply programs in developing countries

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 16 publications
(35 reference statements)
2
34
0
Order By: Relevance
“…While CBM schemes often appear sensible in many rural water management contexts, there are inherent technical, social and economic constraints that introduce additional complexity and often inhibit sustained water service provision. In this case, "technical" constraints generally relate to the community's ability to properly operate and repair the water system [17,18]; "economic" constraints refer to the capacity of the community to afford O & M costs [19,20]; and lastly, "social" constraints generally refer to such aspects as the perceived demand for services, community organization and community member satisfaction with the intervention [3,[21][22][23]. As a result of these frequently confounding constraints, many critics state communities inherently lack the necessary capacity to maintain their water systems without the help of the external support of governments or NGOs.…”
Section: Introductionmentioning
confidence: 99%
“…While CBM schemes often appear sensible in many rural water management contexts, there are inherent technical, social and economic constraints that introduce additional complexity and often inhibit sustained water service provision. In this case, "technical" constraints generally relate to the community's ability to properly operate and repair the water system [17,18]; "economic" constraints refer to the capacity of the community to afford O & M costs [19,20]; and lastly, "social" constraints generally refer to such aspects as the perceived demand for services, community organization and community member satisfaction with the intervention [3,[21][22][23]. As a result of these frequently confounding constraints, many critics state communities inherently lack the necessary capacity to maintain their water systems without the help of the external support of governments or NGOs.…”
Section: Introductionmentioning
confidence: 99%
“…Sources: Boesen (1986);Therkildsen (1988); Maganga et al (2002); URT (2008URT ( , 2010URT ( , 2011Cleaver & Toner (2006); Giné & Pérez-Foguet (2008);Jiménez & Pérez-Foguet (2010a); PMO-RALG, undated. *During the colonial era, 'native authority' referred to local council, which is equivalent to district level in the current local government structure.…”
Section: Periodmentioning
confidence: 99%
“…Therkildsen (1988) noted failed attempts in Africa to supply water in the 1960s and 1970s, and Thompson et al ( 2001) found in East Africa that mean water use had declined between 1960s to1990s due to reduced reliability of the piped water supply, as municipal water services could not maintain the infrastructure. As with our review of water resource infrastructure, at the beginning of this section, these failures mark the limits of engineering approaches, and responses have invariably highlighted a need for greater emphasis on economic, social and political aspects, such as the need for greater partnership with communities (Rietveld etal, 2008), management at the lowest appropriate level, community ownership of schemes, full cost recovery for operation and maintenance, recognizing key roles of women and inclusion of the poor (Gine and Perez-Foguet, 2008 We conclude, therefore, that while science and engineering lie at the heart of the ecological principle, and offer potential to deliver fresh impetus in adaptive behavior at a range of scales, these are unlikely to be successful in isolation from economic and political dimensions. This is illustrated by Integrated Water Resource Management (IWRM), a key application of the ecological principle.…”
Section: Technology and Adaptation To Climate Changementioning
confidence: 99%